If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6 = 13x + -21 Reorder the terms: -6 + 8x = 13x + -21 Reorder the terms: -6 + 8x = -21 + 13x Solving -6 + 8x = -21 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -6 + 8x + -13x = -21 + 13x + -13x Combine like terms: 8x + -13x = -5x -6 + -5x = -21 + 13x + -13x Combine like terms: 13x + -13x = 0 -6 + -5x = -21 + 0 -6 + -5x = -21 Add '6' to each side of the equation. -6 + 6 + -5x = -21 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = -21 + 6 -5x = -21 + 6 Combine like terms: -21 + 6 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 1/X-1/9=4/9-2/3X | | 2u/7=8 | | (50+7x)+3x=70 | | 6xy-2x+3cy-c= | | 8x-6=x+4 | | U^4w^4-u^4=0 | | 12x+(9x-3)-(10x-2)=12 | | 11/4-21/16 | | Y=11-6x/4 | | 5h+6(8h-1)= | | 4/9=2u | | 25d+50=175 | | 15x+5=14x+11 | | a=1/2bh;b=10,h=8 | | x+(x+1)=122-3(x+2) | | n/30-2=3 | | 7=12-5x+4y | | 7f-3=39 | | x-3/5=-1 | | 46-2=8 | | 3x^4-14x^2-24=0 | | 50e-1=799 | | y-(-5)=9x+18 | | a/8-2=8 | | 2-x/2=8-x/3 | | 4(g+8)+7+4g= | | 11k-5=61 | | 8y=2x-48 | | 15y+10=85 | | u^3=27 | | 2-x+9=3x+8 | | (x-45)+(x-45)+(x-45)+2x=540 |